Effect of Fundamental Factors and Systematic Risk on Share Prices in Service Companies Listed on Indonesia Stock Exchange : Pengaruh Faktor Fundamental dan Risiko Sistematis Terhadap Harga Saham Pada Perusahaan Jasa yang Terdaftar Di Bursa Efek Indonesia - hosana situmeang, nike (International Journal of Management and Business (IJMB), 2023)
The purpose of this study was to determine the effect of Fundamental Factors and Systematic Risk on Stock Prices listed on the Indonesian stock exchange. The independent variables used are Fundamental Factors and Systematic Risk. The dependent variable used is the Stock Price. The population in this study is the Fundamental Factor, Systematic Risk, and Stock Price data on Service Companies listed on the Indonesia Stock Exchange for 5 years from 2014-2018. The sample in this study is service companies listed on the Indonesia Stock Exchange (IDX). Data analysis techniques in this study include multiple linear regression. The test results in this study indicate that the Fundamental Factor variable has a significant effect on Stock Prices. From the results of testing the variables above, the Fundamental Factors show the tcount of 2.302> the value of ttable of 1.973 with a significance value of 0.023 <0.05 .. Systematic Risk Variables affect the Stock Price. From the results of testing the variables above, Systematic Risk shows that the t-value of 2.459> t-table value of 1.973 with a significance number of 0.015 <0.05. Together Fundamental Factors and Systematic Risk together have a significant effect on the Share Price with figures that the significant value is 0.005 <0.05 and Fcount> Ftable, where the Fcount is 5.413> Ftable for 3.05.